Integrasi Sosial-Budaya Komunitas Tionghoa di Kota Padang: Studi tentang Adaptasi Lokal dan Perpaduan Budaya dengan Masyarakat Minangkabau - Ovilly Agnesia; Elida Elida; Anni Faridah; Kasmita Kasmita (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2026)
The Chinese community represents one of the ethnic groups with a long-standing history of socio-cultural interaction with the Minangkabau society in Padang City. This study aims to examine the process of socio-cultural integration of the Chinese community within the Minangkabau society, particularly in relation to local adaptation and cultural assimilation in everyday social life. This research employs a descriptive qualitative approach. Data were collected through participant observation and in-depth interviews with key informants, including the Secretary General of HTT Central Padang, local Minangkabau community members, and individuals from the Chinese community. In addition, document analysis of relevant historical and cultural records was conducted to support the findings. The results indicate that the Chinese community in Padang City has undergone a strong process of cultural localization through intensive interaction with the Minangkabau society. Cultural assimilation is reflected in the use of local language in daily communication, intermarriage practices, and adaptation to local social and cultural norms. One notable form of integration is observed in wedding ceremonies, where the Chinese community accommodates the provision of halal food as a form of respect for Minangkabau cultural values. Despite these adaptations, the Chinese community continues to preserve its cultural identity amid contemporary socio-cultural dynamics. The findings suggest that socio-cultural integration between the Chinese community and the Minangkabau society in Padang occurs harmoniously through processes of adaptation, tolerance, and mutual respect, ultimately enriching local cultural diversity.